Radiological fibrosis score is strongly associated with worse survival in rheumatoid arthritis-related interstitial lung disease. Issue 1 (2nd January 2019) - Ito, Yuhei; Arita, Machiko; Kumagai, Shogo; Takei, Reoto; Noyama, Maki; Tokioka, Fumiaki; Nishimura, Keisuke; Koyama, Takashi; Tachibana, Hiromasa; Ishida, Tadashi
Abstract: Objectives: High-resolution computed tomography (HRCT) parenchymal patterns have been used to predict prognosis in patients with interstitial lung disease (ILD). In idiopathic pulmonary fibrosis, the fibrosis score (i.e. the combined extent of reticulation and honeycombing) has been associated with worse survival. This study aimed to identify HRCT patterns and patient characteristics that can predict poor prognosis in rheumatoid arthritis-related ILD (RA-ILD). Methods: We retrospectively analysed 65 patients with newly diagnosed RA-ILD from 2007 to 2016 at Kurashiki Central hospital. Using univariate and bivariate Cox regression analysis, associations with mortality, were identified. Results: During a median follow-up of 56.5 months, 16/65 (24.6%) patients died. Univariate analysis identified six significant poor prognostic factors: lower baseline % predicted forced vital capacity, total interstitial disease score, reticulation score, traction bronchiectasis score, fibrosis score, and definite UIP pattern. Fibrosis score remained to be an independently significant poor prognostic factor of survival on bivariate analysis. Patients with a fibrosis score >20% had higher mortality (HR, 9.019; 95% CI, 2.87–28.35; p  < .05). Conclusion: This study showed that fibrosis score is strongly associated with worse survival in RA-ILD, and patients with fibrosis score >20% had a 9.019-fold increased risk of mortality.